Stiff, lightweight, and programmable architectured pyrolytic carbon lattices via modular assembling - Ali Naderi; Wenhua Lin; Amirreza Tarafdar; Teng Zhang; Yeqing Wang (Communications Materials)
Abstract Recent advances in additive manufacturing have enabled the creation of three-dimensional (3D) architectured pyrolytic carbon (PyC) structures with ultrahigh specific strength and energy absorption capabilities. However, their scalability is limited by reduced strength at larger sizes. Here we introduce a modular assembling approach to scale up PyC lattice structures while retaining strength. Three assembling mechanisms—adhesive, Lego-adhesive, and mechanical interlocking—are explored, demonstrating notably increased specific compressive strength and modulus as size increases, driven by energy release from assembly joint fractures. Practical application is demonstrated by using assembled PyC lattices as the core of an aerospace sandwich structure, significantly enhancing indentation resistance compared to conventional aramid paper honeycomb core. The method also enables versatile designs, including curved structures for space debris protection and bio-scaffold applications. This scalable approach offers a promising pathway for integrating PyC structures into large-scale engineering applications requiring superior mechanical properties and programmability in complicated shape design.